The effectiveness of patient-centered care vs. usual care in type 2 diabetes self-management: A systematic review and meta-analysis - Asmat, Kainat; Dhamani, Khairunnisa; Gul, Raisa; Froelicher, Erika Sivarajan (Frontiers in Public Health, 2022)
Background Patient-centered care in diabetes self-management might be a significant factor in improving health outcomes of adults with type 2 diabetes, yet the supporting evidence is inadequate. This review aimed at assessing the effectiveness of patient-centered self-management care interventions on glycemic control (HbA1c) and self-care behaviors compared with usual care. Methods CINAHL, PubMed, Cochrane Library, Google Scholar, and the HEC Digital Library were searched for studies in English language that assessed patient-centered self-management educational and/or behavioral interventions in adults aged 18 years or older with type 2 diabetes from 2005 to 2020. Interventional studies with at least 3 months of follow-up and reporting on self-care outcomes such as glycemic control (HbA1c) and self-care behaviors including diet control, physical activity, foot care, and medication adherence were included. Results Of 168 identified records, 24 were found eligible comprising 20 RCTs and four QESs with total 4,083 participants. The meta-analysis involved 19 RCTs that provided enough information for a pooled estimate of HbA1c. Compared with the control group, patient-centered self-management interventions significantly lowered HbA1c, −0.56 (95% CI −0.79, −0.32). Stratified analysis for HbA1c with respect to various aspects of intervention showed larger effects in interventions employing both educational and behavioral components, −0.66 (95% CI −0.97, −0.34); spanned over shorter (<03 months) duration, −0.85 (95% CI −1.28, −0.43); administered by nurses, −0.80 (95% CI −1.44, −0.16); and delivered in community settings −0.70 (95% CI −1.14, −0.26). Conclusion This systematic review provided evidence supporting the effectiveness of patient-centered self-management care interventions in improving glycemic control and self-care behaviors in adults with type 2 diabetes and identified key features of intervention contributing toward success.